Surface gloss, gloss retention, and color stability of 2 nano-filled universal resin composites - Molina, Gustavo Fabián (2022)
Fil: Molina, Gustavo Fabián. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Materiales Dentales. Argentina.